An Expanded Spectrum of High-Grade B-Cell Non-Hodgkin Lymphomas Involving the Cervicovaginal Region. (November 2015) - Pather, Sugeshnee; Philip, Vinitha; Lakha, Atul B.; Wiggill, Tracey M.; Suleman, Marie; Patel, Moosa
Abstract : The uterine cervix and vaginal regions are infrequently infiltrated by lymphoma. Involvement of these topographic regions may constitute primary disease or more commonly represent a manifestation of systemic lymphomatous disease. Herein, we report an expanded spectrum of high-grade B-cell non-Hodgkin lymphomas comprising plasmablastic lymphoma (with and without plasmacytic differentiation), ALK-positive large B-cell lymphoma, and diffuse large B-cell lymphoma which involved the uterine cervix and/or vagina of 6 patients at initial diagnosis. These tumors clinically mimicked carcinoma and developed predominantly, but not exclusively, in the setting of human immunodeficiency virus infection.